Fetal Growth Restriction Induces Heterogeneous Effects on Vascular Biomechanical and Functional Properties in Guinea Pigs (Cavia Porcellus) - Garcia-Herrera, C; Cañas-Quezada, D (Frontiers Research Foundation, 2017)
Aim: Fetal growth restriction (FGR) is associated with a variety of cardiometabolic diseases in adulthood which could involve remodeling processes of the vascular walls that could start in the fetal period. However, there is no consensus whether this remodeling affects in a similar way the whole vascular system. We aimed to determine the effects of FGR on the vasoactive and biomechanical properties of umbilical and systemic vessels in fetal guinea pigs. Methods: FGR was induced by implanting ameroid occluders at mid-gestation in uterine arteries of pregnant guinea pigs, whilst the control group was exposed to simulated surgery. At the term of gestation, systemic arteries (aorta, carotid and femoral) and umbilical vessels were isolated to determine ex vivo contractile and biomechanical responses (stretch-stress until rupture) on a wire myograph, as well as opening angle and residual stresses. Histological characteristics in tissue samples were measured by van Gieson staining. Aorta and femoral arteries from FGR showed an increased in biomechanical markers of stiffness (p < 0.01), contractile capacity (p < 0.05) and relative media thickness (p < 0.01), but a reduced internal diameter (p < 0.001), compared with controls. There were no differences in the biomechanical properties of carotid and umbilical from control and FGR fetuses, but FGR umbilical arteries had a decreased contractile response to KCl (p < 0.05) along with a reduced relative media thickness (p < 0.05). Conclusion: Altogether, these changes in functional, mechanical and morphological properties suggest that FGR is associated with a heterogeneous pro-constrictive vascular remodeling affecting mainly the lower body fetal arteries. These effects would be set during a pathologic pregnancy in order to sustain the fetal blood redistribution in the FGR and may persist up to adulthood increasing the risk of a cardiovascular disease. © 2017 Cañas, Herrera, García-Herrera, Celentano and Krause.